The Effect of Salary Satisfaction and Career Development on Turnover Intention Among Gen Z in Indonesia - Supartiwi, Sri Rahma Ayu; Wulansari, Puspita (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the effect of salary satisfaction and career development on turnover intention among Gen Z in Indonesia. The phenomenon of high turnover intention, especially among Gen Z employees, has a significant impact on the sustainability of company human resource systems. This study examines the relationship between salary satisfaction, career development, and the intention to leave the job among young employees. Turnover intention can be minimized by paying close attention to optimal salary satisfaction and employee career development. The purpose of this research is to empirically understand the influence of salary satisfaction and career development in explaining the turnover intention of Gen Z employees in Indonesia. The research was conducted using a descriptive quantitative approach through a survey of 202 respondents. The variables examined include salary satisfaction, career development, and turnover intention. Data analysis was performed using the SEM-PLS method to test the relationships among the variables. The results show that salary satisfaction and career development have a significant effect on turnover intention. In conclusion, salary satisfaction and career development significantly influence turnover intention: the higher the level of salary satisfaction and the stronger the respondents’ perception of career development opportunities provided by the company, the lower their desire to leave the job. Conversely, when salary satisfaction and career development are low, employees’ intention to leave the company tends to increase.